Design approach, mechanical properties and cost-performance evaluation of ultra-high performance engineered cementitious composite (UHP-ECC): A review. (18th July 2022) - Wu, Li-Shan; Yu, Zhi-Hui; Zhang, Cong; Bangi, Toshiyuki
Highlights: The design approach of UHP-ECC was comprehensively reviewed. The mechanical properties of UHP-ECC were systematically discussed. Cost-performance evaluation on the mixture proportion of UHP-ECC was performed. Abstract: Ultra-high performance engineered cementitious composite (UHP-ECC) is gaining significant interest among civil engineering researchers, owing to its excellent mechanical performance. This review is carried out to systematically summarize the design approach and fundamental factors influencing the mechanical properties of UHP-ECC, specifically the fiber parameters, water-binder ratio, nanomaterials, mineral admixtures, cyclic load, and strain rate. Besides, shrinkage performance and shrinkage mitigation approach of UHP-ECC are also discussed in this paper. Finally, the structural application of UHP-ECC is summarized. Based on the Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) method, the economic evaluation of the mixture proportion of current available UHP-ECCs is conducted to suggest the mixture proportions for the design of highly cost-effective UHP-ECC.